(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article examines the main linguistic problems involved in developing a culture of academic writing among university students and young researchers. Particular attention is paid to academic vocabulary, textual coherence, grammatical accuracy, authorial voice, argumentation, citation practices and the influence of the writer’s first language. Academic writing is interpreted not merely as the ability to produce a formally correct text, but as a complex communicative culture based on disciplinary conventions, critical thinking and ethical responsibility. The article also proposes pedagogical approaches for developing students’ academic literacy through genre analysis, corpus-based learning, systematic feedback and regular writing practice.